2021
DOI: 10.3389/fpsyg.2021.571952
|View full text |Cite
|
Sign up to set email alerts
|

Less Expectation, Less Pain: Low Wealth Alleviates Sense of Unfairness

Abstract: Objective wealth plays an important role in social interaction and economic decision making. Previous studies indicate that objective wealth of others may influence the way we participate in resources allocation. However, the effect of objective wealth on responses to fairness-related resource distribution is far from clear, as are the underlying neural processes. To address this issue, we dynamically manipulated proposers’ objective wealth and analyzed participants’ behavior as responders in a modified Ultima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…To motivate the participants' choices, they were told that at the end of the experiment, one of the trials in which they accepted the offer would be selected randomly by the computer and that they would be paid based on that trial. This experimental design is commonly used in UG research (Gaertig et al, 2012 ; Wei et al, 2018 ; Pei et al, 2021 ). We also verbally asked the participants whether they had any questions about the content of the experiment and no one reported that they had doubts about the cover story.…”
Section: Methodsmentioning
confidence: 99%
“…To motivate the participants' choices, they were told that at the end of the experiment, one of the trials in which they accepted the offer would be selected randomly by the computer and that they would be paid based on that trial. This experimental design is commonly used in UG research (Gaertig et al, 2012 ; Wei et al, 2018 ; Pei et al, 2021 ). We also verbally asked the participants whether they had any questions about the content of the experiment and no one reported that they had doubts about the cover story.…”
Section: Methodsmentioning
confidence: 99%
“…Another ERP component that is considered important for the present context is late frontocentral negativity, also termed medial frontal negativity or N450. Multiple studies have described a broad negative component presumably indexing conflict or ambiguity, beginning at 400+ ms poststimulus, with a maximum over frontocentral brain regions (see Larson et al, 2014, for a review; recent research articles on late negativity ERP components indicative of conflict processing include Chouiter et al, 2014; Kałamała et al, 2020; Pei et al, 2021; Rey-Mermet et al, 2019; and Wagner-Altendorf et al, 2020). For implicit social cognition, the late negativity or frontal slow wave ERP component is thought to reflect the implementation of conflict resolution in order to overcome the prepotent (biased) response tendency (Bartholow, 2010).…”
Section: Electrophysiological Measuresmentioning
confidence: 99%